(untitled) (Eurasian Journal of Ecology, 2025)
The negative consequences of cities in terms of development are the increase in wastewater volumes and excessive pollution due to the increase in the proportion of impermeable surfaces, the increase in the types of technogenic impurities and their concentration in surface wastewater. These problems emphasize the relevance of surface wastewater treatment in cities. The main part of pollutants contained in surface wastewater is washed off the surface of catchment basins. Thus, the main part of suspended substances of mineral and organic origin, oil products and heavy metals gets into surface wastewater. The objective of the proposed research work is based on the kinetic study of the absorption of oil products and heavy metals of urban surface wastewater by natural sorbents perlite and vermiculite. Maintaining high efficiency of the biofilter under conditions of low activity of plants and soil microorganisms is ensured by the presence in the filter medium of components with sorption and ion-exchange properties such as perlite and vermiculite. The methodical approach allowed to fully describe the adsorption isotherms of pollutants by the Freundlich model and showed a high correlation coefficient (R2> 93-98). In addition, the processing of the obtained experimental data and the determination of the sorption indices of the sorbents were carried out using the Langmuir monomolecular sorption theory, which fully describes the L-type isotherms. A complex of polycomponent sorbents based on natural perlite, vermiculite and construction sand allows for the purification of surface wastewater from pollutants in a sustainable and environmentally friendly way. The results obtained during the research and the scientific conclusions based on them can form the basis for future research aimed at ensuring the safety of pollution of the Koskorgan Reservoir by sorption purification of surface wastewater in the city of Kentau, Turkestan region. Keywords: surface wastewater, pollutants, petroleum products, heavy metals, sorption purification